Genome-Wide Characterization of Superoxide Dismutase (SOD) Genes in Daucus carota: Novel Insights Into Structure, Expression, and Binding Interaction With Hydrogen Peroxide (H2O2) Under Abiotic Stress Condition - Zameer, Roshan; Fatima, Kinza; Azeem, Farrukh; ALgwaiz, Hussah I. M.; Sadaqat, Muhammad; Rasheed, Asima; Batool, Riffat; Shah, Adnan Noor; Zaynab, Madiha; Shah, Anis Ali; Attia, Kotb A.; AlKahtani, Muneera D. F.; et al. (Frontiers in Plant Science, 2022)
Superoxide Dismutase (SOD) proteins are important antioxidant enzymes that help the plants to grow, develop and respond to a variety of abiotic stressors. This gene family has been identified in a number of plant species, although not yet in Daucus carota. A total of 9 DcSOD genes, comprising 2 FeSODs, 2 MnSODs, and 5 Cu/ZnSODs, are identified in the complete genome of D. carota, which are dispersed in five out of nine chromosomes. On the basis of phylogenetic analysis, SOD proteins from D. carota could be categorized into two main classes (Cu/ZnSODs and Mn-FeSODs), members of the same subgroups have same subcellular location. The phylogenetic analysis was further validated by sequence motifs, exon-intron structure and 3D protein structures, with each subgroup having similar gene as well as protein structure. Cis-regulatory elements responsive to abiotic stresses were identified in the promoter region which may contribute to their differential expression. Based on RNA-seq data, tissue specific expression revealed that ¬¬three DcSODs had higher expression. Four DcSOD genes had higher expression in abiotic stresses (light and dark). Moreover, these genes were subjected to qPCR analyses under cold, heat, salt and drought stress which also suggested their involvement in response to various environmental stress. SODs are antioxidants and play a critical role in removing reactive oxygen species (ROS) including hydrogen peroxide (H2O2), DcSODs were docked with H2O2 to evaluate their binding. Our findings serve as basis for more functional insights into DcSOD gene family, which will help in determining the molecular mechanism by which DcSOD genes respond to various environmental stresses.